A new species of gall midge (Diptera: Cecidomyiidae) damaging ornamental Callistemon (Myrtaceae) in Australia - Kolesik, Peter; Manners, Andrew G.; Hills-Hayes, Brent (Zootaxa, 2017)
Callistemon (Myrtaceae) is a plant genus native to Australia with many cultivars grown as ornamentals worldwide. Several orange larvae of an undescribed gall midge (Diptera: Cecidomyiidae) were found feeding within vegetative buds of Callistemon viminalis plants grown in a production greenhouse in Victoria, Australia. Infested buds stopped their development and, following the departure of larvae, turned necrotic. Pupation took place in the soil. Young potted plants were infested and severely retarded in their overall growth. The new species is described and named Dasineura callistemoni Kolesik sp. nov.